2006
DOI: 10.1177/0163278706290409
|View full text |Cite
|
Sign up to set email alerts
|

What's Next for Translation Research?

Abstract: The National Institutes of Health (NIH) are under increasing pressure to identify practical, cost-effective interventions, therapies, and medications. Overall, the public health impact could be substantial if effective science-based prevention and treatment programs were implemented on large scales with sufficient fidelity. Yet penetration of even the most successful interventions rarely occurs at a quick pace. Research-to-practice gaps are pervasive throughout various fields of behavioral health and safety. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 50 publications
0
41
0
1
Order By: Relevance
“…Although more difficult to measure, commitment to serve particular populations, organizational support for programs, stability of resources and personnel dedicated to the intervention, and organizational values and mission, also bear on the process of implementation (Ginexi & Hilton, 2006; Rohrbach, Grana, Sussman & Valente, 2006). Miller and Shinn (2005) define organizational values as including the “values about what its members believe it ought to accomplish in the world and also about what its members think is good, local prevention practice for its target population” (Miller & Shinn, 2005, p. 172).…”
Section: Introductionmentioning
confidence: 99%
“…Although more difficult to measure, commitment to serve particular populations, organizational support for programs, stability of resources and personnel dedicated to the intervention, and organizational values and mission, also bear on the process of implementation (Ginexi & Hilton, 2006; Rohrbach, Grana, Sussman & Valente, 2006). Miller and Shinn (2005) define organizational values as including the “values about what its members believe it ought to accomplish in the world and also about what its members think is good, local prevention practice for its target population” (Miller & Shinn, 2005, p. 172).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that a major goal of SUD research is the successful implementation of new practices in the field (Ginexi & Hilton, 2006) and the public health concerns regarding high smoking rates among SUD patients (Guydish et al, 2011), our finding of a significant positive relationship between TC availability and use of TCS with patients who smoke has practical implications. For instance, it seems advisable to clearly communicate to counselors about available pharmacotherapies and behavioral treatments for TC in their treatment programs to promote the use of evidence-based TCS.…”
Section: Discussionmentioning
confidence: 84%
“…Ginexi and Hilton (2006) suggested that program costs vary widely across implementations. Differing population cultural characteristics, agency settings, and existing infrastructures can drive those variations (Chatterji, Caffray, Jones, Lillie-Blanton, & Werthamer, 2001; Suter, 2010).…”
Section: Discussionmentioning
confidence: 99%